A pilot study of blood microRNAs and lung function in young healthy adults with fine particulate matter exposure - Zhou, Tianyu; Yu, Qing; Sun, Chao; Wang, Yunxia; Zhong, Yijue; Wang, Guangfa (Journal of Thoracic Disease, 2018)
Fine particulate exposure (PM2.5) is a risk factor of pulmonary diseases such as chronic obstructive pulmonary disease (COPD), but the mechanism underlying was not clear. Recent studies found blood microRNAs (miRNAs) are potential indicators of either COPD or PM2.5 exposure, but these results had no unified conclusions. We suggested it was more targeted to find disease related miRNAs first and then observe them during PM2.5 exposure. Firstly, in order to screen COPD associated miRNAs, we identified differentially expressed blood miRNAs contrasting COPD participants (n=6) without diagnose of COPD or related treatment before and matched control (n=6). In total, 21 miRNAs were differentially expressed in COPD individuals and expression of miR-495-3p, miR-223-5p and miR-194-3p were further validated using qRT-PCR. The results showed miR-495-3p and miR-223-5p significantly increased whereas miR-194-3p decreased marginally (P=0.058) in COPD participants. Secondly, in order to recognize the relevance between these miRNAs and PM2.5 exposure, we designed an independent time-series study nested within “low-high-low” pollution levels. The expression of blood miR-495-3p, miR-223-5p and miR-194-3p were detected before and after exposure (n=8). The results showed expression of miR-223-5p increased significantly while expression of miR-194-3p decreased significantly after exposure. The Pearson analysis showed only miR-194-3p showed a positive statistically correlation with lag0–1 forced expiratory volume in one second (FEV1) and forced vital capacity (FVC) during exposure of PM2.5. So miR-194-3p might be a potential regulator in the toxicological pathways of both PM2.5 exposure and COPD. As this was a pilot study, formal and large-scale studies should be planned in the future.